FORENSIC AUDIT - Rozas Flores, Alan Errol (2009)
The forensic audit is an audit specialist in obtaining evidence to turn them into tests, which are presented in the forum that is in the courts of justice, in order to check crime or settle legal disputes. Currently, major efforts are being carried out by compliance audits and comprehensive audits need to be retrofitted with legal research, to minimize the impunity that comes before economic and financial crimes, such as administrative corruption, corporate fraud and money laundering assets. Prevent, detect, investigate and verify these crimes, requires deep knowledge and skills in accounting and finance, legal, and research, to provide convincing evidence to get the required justice for their judgments. The types of fraud that auditors consider when auditing the financial statements are basically: fraudulent financial reporting and misappropriation of assets. The auditors are responsible for obtaining reasonable assurance that material errors are detected, either due to errors or fraud. In these times when companies are more exposed to fraud, the auditor is hired to review its control to discover the factors that fraud and recommend mitigation programs, helping them from presenting rare or its level is low. Because it is the responsibility of management of the entity to establish adequate control systems and monitor them to function properly, the administration needs to hire a public accountant and auditor Phishing to support it with that work, as this will source tips for establishing measures to prevent or deter the risk of fraud.